Dark Night, Brilliant Star - Lantry, Eileen W.; Nang ChanYeema (Mountain View, CA USA Pacific Press Publishing Association, 1981)
Story of the mission work of Abram La Rue in Hong Kong.
Keywords: Adult Nonfiction